Practice Patterns and Variability in Intraoperative Opioid Utilization: A Report From the Multicenter Perioperative Outcomes Group. (21st July 2021) - Naik, Bhiken I.; Kuck, Kai; Saager, Leif; Kheterpal, Sachin; Domino, Karen B.; Posner, Karen L.; Sinha, Anik; Stuart, Ami; Brummett, Chad M.; Durieux, Marcel E.; Vaughn, Michelle T.; Pace, Nathan L.; et al.
Abstract : BACKGROUND: Opioids remain the primary mode of analgesia intraoperatively. There are limited data on how patient, procedural, and institutional characteristics influence intraoperative opioid administration. The aim of this retrospective, longitudinal study from 2012 to 2016 was to assess how intraoperative opioid dosing varies by patient and clinical care factors and across multiple institutions over time. METHODS: Demographic, surgical procedural, anesthetic technique, and intraoperative analgesia data as putative variables of intraoperative opioid utilization were collected from 10 institutions. Log parenteral morphine equivalents (PME) was modeled in a multivariable linear regression model as a function of 15 covariates: 3 continuous covariates (age, anesthesia duration, year) and 12 factor covariates (peripheral block, neuraxial block, general anesthesia, emergency status, race, sex, remifentanil infusion, major surgery, American Society of Anesthesiologists [ASA] physical status, non-opioid analgesic count, Multicenter Perioperative Outcomes Group [MPOG] institution, surgery category). One interaction (year by MPOG institution) was included in the model. The regression model adjusted simultaneously for all included variables. Comparison of levels within a factor were reported as a ratio of medians with 95% credible intervals (CrI). RESULTS: A total of 1, 104, 324 cases between January 2012 and December 2016 were analyzed. The median (interquartile range) PME and standardized by weight PME per case for the study period were 15 (10–28) mg and 200 (111–347) μg/kg, respectively. As estimated in the multivariable model, there was a sustained decrease in opioid use (mean, 95% CrI) dropping from 152 (151–153) μg/kg in 2012 to 129 (129–130) μg/kg in 2016. The percent of variability in PME due to institution was 25.6% (24.8%–26.5%). Less opioids were prescribed in men (130 [129–130] μg/kg) than women (144 [143–145] μg/kg). The men to women PME ratio was 0.90 (0.89–0.90). There was substantial variability in PME administration among institutions, with the lowest being 80 (79–81) μg/kg and the highest being 186 (184–187) μg/kg; this is a PME ratio of 0.43 (0.42–0.43). CONCLUSIONS: We observed a reduction in intraoperative opioid administration over time, with variability in dose ranging between sexes and by procedure type. Furthermore, there was substantial variability in opioid use between institutions even when adjusting for multiple variables.